Factors Affecting the Capital Structure Of Manufacturing Companies In The Basic Industry and Chemical Sub-Sector Listed On the Indonesia Stock Exchange for the 2017-2019 Period - Tina Novianti Sitanggang; Febrina Theresia Lubis; Siti Tiadora (Institute of Computer Science (IOCS), 2021)
This study aims to discuss whether the capital structure, firms size, dividend payout ratio and sales growth affect the company's capital structure. The companies used in the study are Manufacturing companies on the Indonesia Stock Exchange. The data analysis method used is the classical assumption test and multiple linear analysis. Based on the results of the analysis, it is stated that the firms size has a negative effect, while the capital structure, dividend payout ratio and sales growth have no significant effect on the company.